Studi persepsi pengunjung pada Taman Janggan, Denpasar - Aldiguna, I Gde Andre; Semarajaya, Cokorda Gede Alit; Mayun, Ida Ayu (Jurnal Arsitektur Lansekap, 2019)
Study of user perception in Janggan Park, Denpasar. Janggan Park is a park located in Denpasar City with designed like the janggan kite which was inaugurated on January 5, 2017 by the Vice Governor of Bali. Janggan park there is also a children's play ground and gym facilities. The purpose of this study is to measure the visitor's perception of the beauty, comfort, and safety of Janggan Park in Denpasar and to provide some input to the manager or agency concerned in order to improve the quality of the site. The method used in this research was direct observation to the field, interview, and questionnaire. Based on the research conducted, the results showed that the perception of visitors about the beauty of Janggan Park was beautiful, but there are some part in the garden were less beautiful, that is gym area. The visitor's perception of comfort at Janggan Park was comfortable. Then, the visitor's perception about the secure at Janggan Park was safe. According to the visitor perception of cleanliness at Janggan Park still less clean and need more attention on maintenance because cleanliness also influence the beauty, comfort, and visitor safety. It can be suggested that the manager need to improve the hygiene, supervision, and to improve exsisting facility in Janggan Park.